Experiencias de trabajo docente, análisis de caso en el Colegio “Jatari Unancha” del Cantón Pagua - Yanchaliquin Chimborazo, Cesar Aurelio (2016)
In modern times the education has been making frequent and significant changes, in our country one of the most profound changes has been the teaching of content proposed by updating and strengthening curriculum proposed by the new Ecuadorian curriculum, where the practice of classroom is fundamental when it comes to the teaching experience, since it is more important than theoretical knowledge and pedagogical tools that will acquire. This case analysis was performed using a qualitative research, through interviews with teachers from all areas of knowledge College "Jatari Unancha", retrieved as a result of the history of the professional performance of three of them in his arduous teaching but on the entire process of teaching - learning of each teacher, versions and assertions that will serve as advisory support so that others can be inserted and undertake the path of the induction of knowledge, situation which is defined as the productive work of men and women of good, useful in the solution of the multiple needs of their own contexts of life.